Formation of a combined electron-hole emission state in the LiRbSO4 – Eu phosphor - Nurakhmetov, T.N.; Bakhtizin, R.Z.; Tolekov, D.A.; Shamieva, R.K.; Salikhodzha, Zh.M.; Sadykova, B.M.; Yusupbekova, B.N.; Pazylbek, S.A.; Bairbaeva, G.B.; Rakhymzhanov, B.M. (Karagandy University of the name of acad. E.A. Buketov, 2024)
In the irradiated phosphor LiRbSO4 Eu , the mechanisms of formation of the induced or combined electron- emitting state at 3.1-2.94 eV were studied using optical and thermal activation spectroscopy methods. It has been shown experimentally that the combined electron-emitting state of the phosphor is formed from the electron states of impurity and intrinsic electron and hole trapping centers of 2 4 Eu SO    and 3 4 4 SO SO    . Electron and hole trapping centers are created by irradiating the phosphor with photons exceeding the width of the forbidden band of the matrix, where free electrons are created in the conduction band and a hole in the valence band. The trapping center is formed by the capture of free electrons by impurities and anionic complexes according to the reaction 3 2 Eu e Eu      , 2 3 4 4 SO e SO      . In one process with electron centers, holes in the form of 2 4 SO  are localized. Thus, impurity and intrinsic 2 4 Eu SO    and 3 4 4 SO SO    electronhole trapping centers are formed. Similarly, trapping centers are formed as a result of charge transfer from the excited anion of the 2 4 SO  complex to the 3 Eu  impurities and to the neighboring 2 4 SO  anions according to the reaction ( 2 3 O Eu    ) and ( 2 2 4 O SO    ), and localized holes are also formed in one act along with it. Combined electron-emitting states consisting of impurity and intrinsic electron states are excited by photons with energies of ~4.0 eV and ~4.5 eV.
LiRbSO4 – Eu люминофорындағы біріктірілген электронды-кемтік сәулелену күйінің түзілуі
Образование комбинированного электронно-дырочного излучательного состояния в люминофоре LiRbSO4–Eu
Keywords: electron; hole; recombination emission; intrinsic emission; sulfate; excitation